CYTOCHEMICAL STUDY ON THE PANCREAS OF THE GUINEA PIG : VII. Effects of Spermine on Ribosomes - Siekevitz, Philip (The Rockefeller University Press, 1962)
Pancreatic ribosomes (guinea pig) aggregate and lose upon treatment with polyamines, particularly spermine, their bound secretory enzymes. Spermine, at 0.5 mM, for example, causes the release of about 85 per cent of the chymotrypsinogen and RNase, and from 85 to 100 per cent of the ribosomal amylase. At the same time, the particles lose about 10 per cent of their RNA, 7 to 24 per cent of their total protein, and from 75 to 100 per cent of their Mg(++). Observations with the electron microscope confirm the heavy agglutinating of the ribosomes but otherwise show little change in the structure of the particles. Using radioactive spermine it was found that, concomitant with the loss of bound enzymes and Mg(++) from the ribosomes, spermine became bound to the particle. The extent of binding ranged from 0.29 to 1.49 µmoles per 10µmoles RNA-P. The bound radioactive spermine can be removed by subsequent treatment of the ribosomes with GTP, ATP, or P-P, which treatment also removes most of the RNA of the particles, leaving behind ribosomes with a much lower RNA/protein ratio. From this evidence it was inferred that spermine, in releasing the Mg(++) of the particle, becomes salt-linked to the free phosphate hydroxyl groups of the RNA. Freshly isolated pancreatic and hepatic ribosomes contain very little spermine, about 0.1 to 0.2 µmoles polyamine/10 µmoles RNA-P. The results are discussed in terms of the linkages between the structural protein, the bound secretory enzymes, and the RNA of the ribosomes.